2010
DOI: 10.3109/01612840903267638
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women: The Phenomenon of Workplace Violence Against Nurses

Abstract: Registered nurses have been the recipients of an alarming increase in workplace violence (WPV). Emergency and psychiatric nurses have been found to be the most vulnerable and yet few solid reporting procedures exist to fully account for a true number of incidents. Further compounding the problem is the lack of a standard definition of violence to guide reporting procedures, interventions, legislation, and research. While there are certain risk factors that not only predispose the nurse and the patient to WPV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 41 publications
1
59
1
1
Order By: Relevance
“…The absence of a class characterized by violence occurring across contexts is interesting given the literature suggesting the co-occurrence of childhood abuse and adult victimization (Bensley, et al, 2003; Engstrom, El-Bassel, Go, & Gilbert, 2008) as well as WPV and abusive relationships or childhood abuse (Child & Mentes, 2010; Little, 1999). One possible explanation for the current finding is that women who experience violence across contexts may have chosen not to participate in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a class characterized by violence occurring across contexts is interesting given the literature suggesting the co-occurrence of childhood abuse and adult victimization (Bensley, et al, 2003; Engstrom, El-Bassel, Go, & Gilbert, 2008) as well as WPV and abusive relationships or childhood abuse (Child & Mentes, 2010; Little, 1999). One possible explanation for the current finding is that women who experience violence across contexts may have chosen not to participate in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Poly-victimization may also occur across different contexts as many forms of childhood abuse, including sexual (Arata, 2002; Messman & Long, 1996), physical (Bensley, Van Eenwyk, & Wynkoop Simmons, 2003), and physical abuse between parents/caregivers (Bensley, et al, 2003; Ehrensaft et al, 2003), have been associated with women's subsequent victimization in adulthood. Additionally, abuse in a relationship, whether current or previous, has been indicated to elevate risk for WPV (Child & Mentes, 2010). …”
mentioning
confidence: 99%
“…[11,[17][18][19] Diğer yandan, toplumda agresyon ve şiddet eylemlerinin modern sosyal örüntüleri yansıtır şekilde artışı, bu tür olayların sağlık kurumlarında ve psikiyatri servislerinde de çoğalması-nı kaçınılmaz hale getirebilmektedir. [20] Psikiyatri servislerinde agresyon ve şiddetin ele alındığı çalışmalarda, agresyona en fazla maruz kalanların bu servislerde çalışan hemşireler olduğu ve hatta hasta agresyonunun hemşirelik mesleğini bırakmaya neden olan önemli faktörler-den biri olduğu belirtilmektedir. [4,8,11,[21][22][23][24][25][26][27][28][29][30][31] Psikiyatri servislerinde agresyon ve şiddetin incelendiği çalışmalara göz atıldı-ğında, dünya genelinde oldukça yaygın bir şekilde görüldüğü dikkati çekmektedir:…”
Section: Epidemiyolojiunclassified
“…Certain occupations have an obvious potential for violence, such as law enforcement, and these are acknowledged by society as such. There is generally a more infrequent reference to the risk of violence in the health care sector, although the incidence is significantly higher and often underreported (Child & Mentes, 2010). Gallant-Roman (2008) reported that the cost of workplace violence was estimated to be $4.2 billion annually in 2001.…”
Section: Workplace Violencementioning
confidence: 99%